Intravenous Leiomyoma with Extension to the Heart: A Case Report and Review of the Literature. (29th September 2013) - Demirkiran, Fuat; Sal, Veysel; Kaya, Umit; Alhan, Cem; Tokgozoglu, Nedim
Abstract : Introduction . Intravenous leiomyomatosis with cardiac extension is an extremely rare uterine tumor. We report here a case of intravenous leiomyoma extending to the right atrium, diagnosed in a patient having leiomyoma. Case Presentation . A 39-year-old woman with no symptoms and a past medical history of two myomectomy operations (7 and 3 years previously) was admitted to our clinic for routine control. We detected a uterine fibroid of 8 centimeters and 4 small solid masses of 1-2 centimeters near the uterus and ovaries at vaginal ultrasonography. Computed tomography (CT) was performed to investigate the abdominal cavity. It revealed a mass originating from the left common iliac vein, which invaded the inferior vena cava (IVC) and extended to the right atrium in addition to the uterine fibroids and pelvic masses. The operation was performed with a combined team of gynecologists and cardiac surgeons and a one-stage operation was accomplished. The postoperative course was uneventful. Conclusion . Abdominal CT is a useful imaging technique for the diagnosis of unusual pathology in a patient with uterine fibroid having suspicious pelvic masses. Also, when a right atrial mass is identified in a female with a prior history of hysterectomy because of leiomyoma or in whom there is a uterine myoma, then intravenous leiomyomatosis should be considered.